2011
DOI: 10.1029/2010gc003450
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on afterslip and steady state and transient rheology based on postseismic deformation and geoid change caused by the Sumatra 2004 earthquake

Abstract: [1] The commonly used rheological model for the Earth's mantle when considering geological time scales (mantle convection) is the viscoelastic Maxwell model, which assumes a steady state creep process. However, application of this model to phenomena on shorter time scales, such as postglacial rebound or postseismic relaxation, leads to difficulties in finding a consistent interpretation of obtained viscosities. Using standard Maxwell viscosity of 1e19 Pa s to analyze postseismic near-field GPS time series from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 35 publications
(49 reference statements)
10
57
2
Order By: Relevance
“…Asthenosphere viscosity † Asthenosphere steady-state viscosities estimates for subduction zones are commonly on the order of 10 19 Pa s, based on observations of postseismic deformation (generally estimates are in the range [10 18 -10 20 ] see table 1 of Wang (2007)). This viscosity estimate is in line with results from recent studies that interpret postseismic deformation after recent megathrust earthquakes, such as the 2004 Sumatra-Andaman earthquake (Hoechner et al, 2011;Broerse et al, 2015), the 2010 Maule earthquake (Klein et al, 2016;Bedford et al, 2016) or 2011 Tohoku earthquake (Hu et al, 2016). However, the asthenosphere viscosities reported for subduction zones may be more applicable to the mantle wedge than the suboceanic asthenosphere Hirth and Kohlstedt (2003), for which we adopt the higher value of ≈ 10 20 Pa s (Hu et al, 2004;Broerse et al, 2015).…”
Section: Discussion Of the Slab Break-off Modelsupporting
confidence: 65%
“…Asthenosphere viscosity † Asthenosphere steady-state viscosities estimates for subduction zones are commonly on the order of 10 19 Pa s, based on observations of postseismic deformation (generally estimates are in the range [10 18 -10 20 ] see table 1 of Wang (2007)). This viscosity estimate is in line with results from recent studies that interpret postseismic deformation after recent megathrust earthquakes, such as the 2004 Sumatra-Andaman earthquake (Hoechner et al, 2011;Broerse et al, 2015), the 2010 Maule earthquake (Klein et al, 2016;Bedford et al, 2016) or 2011 Tohoku earthquake (Hu et al, 2016). However, the asthenosphere viscosities reported for subduction zones may be more applicable to the mantle wedge than the suboceanic asthenosphere Hirth and Kohlstedt (2003), for which we adopt the higher value of ≈ 10 20 Pa s (Hu et al, 2004;Broerse et al, 2015).…”
Section: Discussion Of the Slab Break-off Modelsupporting
confidence: 65%
“…Moreover, postseismic displacements calculated by models with biviscous Burgers rheologies are often described by logarithmic functions (Hetland and Hager 2006). Hoechner et al (2011) also proposed that the response of a Burgers body consists of two superposed exponential decays.…”
Section: Relationship Between Postseismic Deformation Mechanisms and mentioning
confidence: 99%
“…A few papers [183,192,193] have modelled the observed postseismic signal after the Sumatra-Andaman event as the result of viscoelastic relaxation. All studies agree that relaxation is characterized by a transient phase with fast flow followed by a slower steady-state phase.…”
Section: Seismologymentioning
confidence: 99%
“…Panet et al [192], however, invoked the presence of a small amount of afterslip, on the basis of GRACE data and a few GPS sites at about 500-1000 km from the fault. Following a different approach, Hoechner et al [193] started from GPS data to refine the coseismic model and to reduce the number of candidate postseismic models, and to estimate the optimal crustal thickness. Then, they used GRACE data to discriminate between two alternatives, the combination of a Maxwell model and afterslip vs. a Burgers model, and found that the Burgers model provides a much better fit to gravity observations ( Figure 18).…”
Section: Seismologymentioning
confidence: 99%